INTEGRATION OF SPORT VALUES THROUGH FOOTBALL IN THE CONTEXT OF POSITIVE YOUTH DEVELOPMENT - Risyanto, Aris; Subarjah, Herman; Ma'mun, Amung; Nuryadi, Nuryadi (ASEAN Journal of Sport for Development and Peace, 2023)
The purpose of this study is to ascertain the impact of incorporating sport values into a young development training program for soccer. An experiment using a model of quasi-experimental design is the research technique employed. A questionnaire was utilized as the method of data collecting in this study. Purposive sampling was utilized as the sample method. 30 young men between the ages of 15-20 made up the sample, and they were split into three groups: group a received football training with the integration of sport values from 15 youths; group b received soccer training without the integration of sport values from 15 youths. The findings demonstrated that the development of sport values was greater in the soccer training group (group a) that had sport values incorporated into the curriculum than in the soccer training group (group b) that did not. Adolescents' daily lives can benefit from the development of youth sport values, which can be used to help them deal with the demands and difficulties of life while also reaping the advantages of sport values.